ARP and QPP Interleavers for LTE Turbo Coding - Nimbalker, A.; Blankenship, Y.; Classon, B.; Blankenship, T.K. (2008 IEEE Wireless Communications and Networking Conference, 2008)
The Long Term Evolution (LTE) of the WCDMA standard requires turbo decoding throughputs of up to 100 Mbps. Unfortunately, the existing WCDMA turbo interleaver does not permit an efficient high throughput implementation. The almost regular permutation (ARP) and quadratic polynomial permutation (QPP) interleavers were proposed to rectify this situation with QPP selected for LTE. In this paper, the interleavers are compared and a full suite of LTE designs and performance results for both are presented.